HIF-2α regulates proliferation, invasion, and metastasis of hepatocellular carcinoma cells via VEGF/Notch1 signaling axis after insufficient radiofrequency ablation - Yang, Yongguang; Chen, Weifeng; Mai, Weiheng; Gao, Yi (Frontiers in Oncology, 2022)
Background and Aims Although insufficient radiofrequency ablation (RFA) promotes the recurrence and metastasis of liver cancer, the underlying mechanism remains unclear. This study aimed to investigate the role and mechanism of HIF-2α in hepatocellular carcinoma cells (HCCs) after Insufficient RFA. Methods We established a model of insufficient RFA in MHCC97H hepatoma cells and screened for stable sublines. We inhibited HIF-2α expression in the Insufficient RFA group using PT2385 and assessed the resulting changes in proliferation and biological function of HCCs. Cell viability and proliferation were detected by the MTT method, and scratch and Transwell chamber invasion tests detected migration and invasion abilities of HCCs. The mRNA and protein expression levels of VEGF, HIF-2α, and Notch1 were detected using qPCR, immunofluorescence, and western blotting. Results Compared with normal HCCs without RFA treatment, insufficient RFA enhanced the proliferation and invasion abilities of hepatocellular carcinoma subline MHCC97H (P < 0.001), as well as their migration ability (P = 0.046). The HIF-2α-specific inhibitor PT2385 downregulated the migration (P = 0.009) and invasion (P < 0.001) of MHCC97H cells but did not affect cell proliferation (P > 0.05). Insufficient ablation increased the mRNA and protein expression of VEGF, HIF-2α, and Notch1 in HCCs, whereas inhibition of HIF-2α reversed these changes. Conclusions Insufficient RFA increases the proliferation, migration, and invasion of HCCs via the HIF-2α/VEGF/Notch1 signaling axis; HIF-2α is a potential target for novel treatments of HCC after insufficient RFA.